Laminin-α4 Is Upregulated in Both Human and Murine Models of Obesity - Goddi, Anna; Carmona, Alanis; Schroedl, Liesl; White, Jeremy M.; Piron, Matthew J.; De Leon, Avelino; Casimiro, Isabel; Hoffman, Alexandria; Gonzalez Porras, Maria A.; Brey, Eric M.; Brady, Matthew J.; Cohen, Ronald N. (Frontiers in Endocrinology, 2021)
Obesity affects nearly one billion globally and can lead to life-threatening sequelae. Consequently, there is an urgent need for novel therapeutics. We have previously shown that laminin, alpha 4 (Lama4) knockout in mice leads to resistance to adipose tissue accumulation; however, the relationship between LAMA4 and obesity in humans has not been established. In this study we measured laminin-α chain and collagen mRNA expression in the subcutaneous white adipose tissue (sWAT) of mice placed on chow (RCD) or 45% high fat diet (HFD) for 8 weeks, and also in HFD mice then placed on a “weight loss” regimen (8 weeks HFD followed by 6 weeks RCD). To assess extracellular matrix (ECM) components in humans with obesity, laminin subunit alpha mRNA and protein expression was measured in sWAT biopsies of female control subjects (BMI<30) or subjects with obesity undergoing bariatric surgery at the University of Chicago Medical Center (BMI>35) both before and three months after surgery. Lama4 was significantly higher in sWAT of HFD compared to RCD mice at both the RNA and protein level (p<0.001, p<0.05 respectively). sWAT from human subjects with obesity also showed significantly higher LAMA4 mRNA (p<0.01) and LAMA4 protein expression (p<0.05) than controls. Interestingly, even though LAMA4 expression was increased in both humans and murine models of obesity, no significant difference in Lama4 or LAMA4 expression was detected following short-term weight loss in either mouse or human samples, respectively. From these results we propose a significant association between obesity and elevated LAMA4 expression in humans, as well as in mouse models of obesity. Further studies should clarify the mechanisms underlying this association to target LAMA4 effectively as a potential therapy for obesity.